PENGARUH SOLVABILITAS, PROFITABILITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN, KOMITE AUDIT, OPINI AUDIT, DAN REPUTASI KAP TERHADAP AUDIT REPORT LAG - Dwi Prasetyo; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This study aims to test the effect of solvency, profitability, firm size, firm age, audit committee, audit opinion, and KAP reputation on audit report lag. In this study, solvency, profitability, firm size, firm age, audit committee, audit opinion, and KAP reputation variables act as independent variables, besides the dependent variable used is audit report lag.The sample in this study is manufacturing and service companies listed on the IDX in 2019-2020 with a total sample of 498 samples. The sample selection is based on the purposive sampling method with the criteria and requirements determined by the researcher. The analytical method used in this research is multiple linear regression analysis.The results of the study explain that simultaneously all independent variables namely solvency, profitability, company size, company age, audit committee, audit opinion, and KAP reputation affect the delay in audit reports. Partially, the results of the study explain that solvency has a positive and significant impact on the audit report lag. Profitability, firm size, firm age, and KAP reputation have a significant negative effect on audit report lag. Meanwhile, the audit committee and audit opinion have a negative but not significant effect on the delay in the audit report.